Mucosal incision‐assisted biopsy versus endoscopic ultrasound‐guided fine‐needle aspiration with a rapid on‐site evaluation for gastric subepithelial lesions: A randomized cross‐over study. Issue 4 (2nd April 2019) - Osoegawa, Takashi; Minoda, Yosuke; Ihara, Eikichi; Komori, Keishi; Aso, Akira; Goto, Ayako; Itaba, Soichi; Ogino, Haruei; Nakamura, Kazuhiko; Harada, Naohiko; Makihara, Kosuke; Tsuruta, Shinichi; et al.
Abstract : Objectives: This study aimed to compare the diagnostic yield of mucosal incision‐assisted biopsy (MIAB) and endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) with a rapid on‐site evaluation (ROSE) for gastric subepithelial lesions (SEL) suspected of being gastrointestinal stromal tumors (GIST) with an intraluminal growth pattern. Methods: This was a prospective randomized, cross‐over multicenter study. The primary outcome was the diagnostic yield of EUS‐FNA and MIAB. The secondary outcomes were the technical success rate, complication rate, procedure time and biopsy frequency. Results: A total of 47 patients were randomized to the MIAB group ( n = 23) and EUS‐FNA group ( n = 24). There was no significant difference in the diagnostic yield of MIAB and EUS‐FNA (91.3% vs 70.8%, P = 0.0746). The complication rates of MIAB and EUS‐FNA did not differ to a statistically significant extent. The mean procedure time in the MIAB group was significantly longer than that in the EUS‐FNA group (34 vs 26 min, P = 0.0011). Conclusions: The diagnostic yield of MIAB was satisfactorily as high as EUS‐FNA with ROSE for gastric SEL with an intraluminal growth pattern.